Finite Element and Multibody Dynamics Analysis of a Ball Mill Glass Crusher. (16th March 2023) - Rishmany, Jihad; Imad, Rodrigue
Abstract : Recycling and sustainability constitute a major challenge to preserve human life quality and ensure a good standard of living for future generations. Like other recyclable waste products, glass waste can be a major problem if it is not recycled. When glass waste is turned into powder, environmental impacts are minimized by reducing or eliminating the dependency on landfills. Within this context, the objective of this work is to design a low-cost glass crusher machine that can be acquired by individuals. For this purpose, a glass crusher machine based on the ball mill concept is designed to transform glass waste into powder of 2 mm particle size. The main enhanced features of this machine with respect to state-of-the-art designs are the continuous feed aspect and the powder discharge technique. The design methodology consisted of mathematical modeling coupled with numerical simulations to ensure a safe and functioning design. This was achieved via different types of simulations using SolidWorks: static stress analysis, free vibration analysis, and motion study. Finally, a market study shows that a breakeven period is reached after a period of 5 months.